Experimental Test of Compressive Strength of Eco-Friendly Concrete Using 0%, 10%, 20% Aren Tree Powder Waste as a Substitute for Fine Aggregate - Nugroho, Guntur (UIN Sunan Gunung Djati Bandung, 2025)
Construction development in Indonesia is experiencing rapid progress, leading to various innovations in concrete mixtures using organic waste. Aren Tree Powder (ATP) waste is a solid waste from the tapioca industry obtained from the extraction process. One way to utilize this waste is by incorporating it into concrete mixtures as a substitute for fine aggregate, thereby reducing waste that pollutes the environment. The purpose of the research is to determine the compressive strength of concrete with a mixture of Aren Tree Powder (ATP) as a substitute for fine aggregate at 0%, 10%, and 20%. The research method used is experimental testing with concrete cylinder test specimens measuring 15cm in diameter and 30cm in height. The number of samples for each mix variation is 3 test specimens. The compressive strength test was conducted on concrete cylinder specimens that had cured for 28 days. The test results show average compressive strength values of 24.01MPa, 23.97MPa, 22.91MPa, at variations of 0%, 10%, 20%. The compressive strength of the concrete decreased by 0.16%, 4.52% for the 10%, 20% variations compared to normal concrete. The conclusion of the research shows that concrete with 10% and 20% variations falls into the medium-strength category, which can be used for reinforced concrete structures